"Liking" and being "liked": How are personality traits and demographics associated with giving and receiving "likes" on Facebook?. (March 2017) - Hong, Cheng; Chen, Zifei (Fay); Li, Cong
Abstract: On social media, users can express their favorable attitudes toward messages that others post by clicking the "like" button. In return, they may also receive "likes" from others for their own posts. This study aims to examine the "liking" behavior on social media by using the theoretical framework of gift giving and impression management. Specifically, the study investigates if and how different personality traits (i.e., self-esteem, empathy, interpersonal generosity, and public self-consciousness) and demographic characteristics (i.e., gender, age, and education) are associated with one's frequencies of giving and receiving "likes" on Facebook. A survey was conducted with 421 Facebook users in the United States. The study results revealed that frequency of giving "likes" was positively associated with both interpersonal generosity and public self-consciousness, but frequency of receiving "likes" was not significantly related to the examined personality traits. Age and gender were significantly associated with frequencies of both giving and receiving "likes." Educational background was negatively associated with giving "likes." Highlights: "Liking" is examined through the lens of gift giving and impression management. People with different "liking" patterns differ in personality and demographics. Giving "likes" is associated with interpersonal generosity and self-consciousness. Receiving and giving "likes" are both associated with age and gender. Giving "likes" is negatively associated with education level.